A Scale to Assess Student Perceptions of Academic Climates - Janz, Teresa A.; Pyke, Sandra W. (Canadian Journal of Higher Education, 2000)
Sandler and Hall (1986) define a chilly academic climate as the "... subtle ways women are treated differently — ways that communicate to women that they are not quite first-class citizens in the academic community" (p. 1). This paper describes the construction of a scale to assess university students' perceptions of the chilly climate. An initial pool of 123 items was refined based on statistical analyses of the responses of 192 students to produce a 28-item Perceived Chilly Climate Scale (PCCS). Factor analysis identified five factors: Climate Students Hear About; Sexist Treatment; Climate Students Experience Personally; Classroom Climate; and Safety. To investigate further the reliability and validity of the scale, the PCCS, an Alienation Scale (Dean, 1961) and the Marlowe-Crowne Social Desirability Scale (Reynolds, 1982) responses were gathered from 327 students. As expected, the PCCS was significantly related to alienation but unrelated to socially desirable responding. Additional evidence supporting the reliability and validity of the PCCS is presented.